Latitudinal Pigmentation Variation Contradicts Ultraviolet Radiation Exposure: A Case Study in Tropical Indian Drosophila melanogaster - Rajpurohit, Subhash; Schmidt, Paul S. (Frontiers in Physiology, 2019)
The effects of ultraviolet radiation (UV) on the animal body have been reported in many studies, and melanin has emerged as a protective mechanism. In smaller insects such as Drosophila, replicated patterns of geographical variation in pigmentation have been observed on multiple continents. Such patterns are particularly pronounced on the Indian subcontinent where several species show a parallel cline in pigmentation traits. However, the potential role of UV exposure in generating the observed patterns of pigmentation variation has not been addressed. Here, we examine the association between UV intensity and body pigmentation in D. melanogaster natural populations collected along the latitudinal gradient of the Indian subcontinent. A strong negative relationship was observed between UV intensity and body pigmentation. This analysis clearly indicates that, in the sampled populations, pigmentation variation is independent of UV exposure and related selection pressures. Patterns of pigmentation in natural populations from the Indian subcontinent are better predicted by latitude itself and temperature-related climatic variables.